Comparison of anisotropic aperture based intensity modulated radiotherapy with 3D-conformal radiotherapy for the treatment of large lung tumors - Simeonova-Chergou, Anna; Abo-Madyan, Yasser; Welzel, Grit; Polednik, Martin; Wenz, Frederik; Lohr, Frank (Radiotherapy and oncology, 2012)
Purpose/objective(s) - IMRT allows dose escalation for large lung tumors, but respiratory motion may compromise delivery. A treatment plan that modulates fluence predominantly in the transversal direction and leaves the fluence identical in the direction of the breathing motion may reduce this problem. - Materials/methods - Planning-CT-datasets of 20 patients with Stage I-IV non small cell lung cancer (NSCLC) formed the basis of this study. A total of two IMRT plans and one 3D plan were created for each patient. Prescription dose was 60Gy to the CTV and 70Gy to the GTV. For the 3D plans an energy of 18MV photons was used. IMRT plans were calculated for 6MV photons with 13 coplanar and with 17 noncoplanar beams. Robustness of the used method of anisotropic modulation toward breathing motion was tested in a 13-field IMRT plan. - Results - As a consequence of identical prescription doses, mean target doses were similar for 3D and IMRT. Differences between 3D and 13- and 17-field IMRT were significant for CTV Dmin (43Gy vs. 49.1Gy vs. 48.6Gy; p<0.001) and CTV D95 (53.2Gy vs. 55.0Gy vs. 55.4Gy; p=0.001). The Dmean of the contralateral lung was significantly lower in the 17-field plans (17-field IMRT vs. 13- vs. 3D: 12.5Gy vs. 14.8Gy vs. 15.8Gy: p<0.05). The spinal cord dose limit of 50Gy was always respected in IMRT plans and only in 17 of 20 3D-plans. Heart Dmax was only marginally reduced with IMRT (3D vs. 13- vs. 17-field IMRT: 38.2Gy vs. 36.8Gy vs. 37.8Gy). Simulated breathing motion caused only minor changes in the IMRT dose distribution (∼0.5-1Gy). - Conclusions - Anisotropic modulation of IMRT improves dose delivery over 3D-RT and renders IMRT plans robust toward breathing induced organ motion, effectively preventing interplay effects.
Gesehen am 20.08.2019
Available online 17 November 2011